Penerapan Rinfo Sebagai Media Pendukung Untuk Proses Pembelajaran Pada Perguruan Tinggi Raharja - Untung Rahardja; Khanna Tiara; Ray Indra Taufik Wijaya (Universitas Raharja, 2014)
Education is an important factor in human life. According to Ki Hajar Dewantara, education is a civilizing process that a business gives high values ??to the new generation in a society that is not only maintenance but also with a view to promote and develop the culture of the nobility toward human life. Education is a human investment that can be used now and in the future. One other important factor in supporting human life in addition to education, which is technology. In this globalization era, technology has touched every joint of human life. The combination of these two factors will be a new innovation in the world of education. The innovation has been implemented by Raharja College, namely the use of the method iLearning (Integrated Learning) in the learning process. Where such learning has been online based. ILearning method consists of TPI (Ten Pillars of IT iLearning). Rinfo is one of the ten pillars, where it became an official email used by the whole community’s in Raharja College to communicate with each other. Rinfo is Gmail, which is adapted from the Google platform with typical raharja.info as its domain. This Rinfo is a medium of communication, as well as a tool to support the learning process in Raharja College. Because in addition to integrated with TPi, this Rinfo was connected also support with other learning tools, such as Docs, Drive, Sites, and other supporting tools.